Окончание -ας- винительного падежа множественного числа древнегреческих имен на -α- и фрагмент Алкмана 17 PMG - Кудулите, А. (Kalbotyra, 1981)
The article deals with the short accusatives plural of α-stems sporadically used in ancient Greek poetry. This short accusatives plural came into being by analogy with athematic stem in the process of the modification of epic formulas, their metrical shape remaining fixed. Alcman must have taken the epic formula μετὰτροπᾰς, with the short ending -ᾰς from Hesiod.